2018
DOI: 10.1051/0004-6361/201834171
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolving the atmosphere of the non-Mira-type AGB star SW Vir in near-infrared molecular and atomic lines with VLTI/AMBER

Abstract: Aims. We present a near-infrared spectro-interferometric observation of the non-Mira-type, semiregular asymptotic giant branch star SW Vir. Our aim is to probe the physical properties of the outer atmosphere with spatially resolved data in individual molecular and atomic lines. Methods. We observed SW Vir in the spectral window between 2.28 and 2.31 µm with the near-infrared interferometric instrument AMBER at ESO's Very Large Telescope Interferometer (VLTI). Results. Thanks to AMBER's high spatial resolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 54 publications
5
9
0
Order By: Relevance
“…As for BK Vir, at first glance, our best continuous multilayer MOLsphere model (PAMPERO) for SW Vir agree within their 1-σ uncertainties with that of discontinuous two-layer solution given by Ohnaka et al (2019), particularly at the first layer, where Ohnaka et al (2019) found 1.3±0.1R (T0 = 2000±100K, N0 = 1−3×10 22 mol/cm −2 ) while our results show at the same size (T0 = 1940 ± 60K, N0 = 10 22.5 − 10 20.5 mol/cm −2 ). However, we find noticeable disagreement for the second layer, especially for NCO where Ohnaka et al (2019) found 2.0 ± 0.2R (T = 1700 ± 100K, N = 2 × 10 19 − 2 × 10 20 mol/cm −2 ) while our results indicate at the same size (T = 1880 − 1903K, N = 10 14.6 −10 17.22 mol/cm −2 ). We attribute this large difference in density, for BK Vir, to the fact that the discontinuous two-layers do not take into account the effect of a continuous MOLsphere which may overestimate the temperaturedensity parameters of a large MOLsphere area when using a single thin layer.…”
Section: Sw Virsupporting
confidence: 72%
See 1 more Smart Citation
“…As for BK Vir, at first glance, our best continuous multilayer MOLsphere model (PAMPERO) for SW Vir agree within their 1-σ uncertainties with that of discontinuous two-layer solution given by Ohnaka et al (2019), particularly at the first layer, where Ohnaka et al (2019) found 1.3±0.1R (T0 = 2000±100K, N0 = 1−3×10 22 mol/cm −2 ) while our results show at the same size (T0 = 1940 ± 60K, N0 = 10 22.5 − 10 20.5 mol/cm −2 ). However, we find noticeable disagreement for the second layer, especially for NCO where Ohnaka et al (2019) found 2.0 ± 0.2R (T = 1700 ± 100K, N = 2 × 10 19 − 2 × 10 20 mol/cm −2 ) while our results indicate at the same size (T = 1880 − 1903K, N = 10 14.6 −10 17.22 mol/cm −2 ). We attribute this large difference in density, for BK Vir, to the fact that the discontinuous two-layers do not take into account the effect of a continuous MOLsphere which may overestimate the temperaturedensity parameters of a large MOLsphere area when using a single thin layer.…”
Section: Sw Virsupporting
confidence: 72%
“…So, and as can be seen, the theoretical spectra of strong molecular or atomic features, which are deduced from only the photospheric models can be highly misleading. This was well demonstrated, in the past, for BK Vir, α Boo and SW Vir by Ohnaka et al (2012); Ohnaka & Morales Marín (2018) and Ohnaka et al (2019) respectively, by using a MOLsphere model of two-layers.…”
Section: Multi-layer Molsphere Model; Pamperosupporting
confidence: 64%
“…atmospheric extension of S Ori in mask C3 is consistent with the previous observations of other AGB stars by Ohnaka et al (2016Ohnaka et al ( , 2019, who showed that their molecular layers are located at ∼1.5 R * and further away. A similar agreement is present in the results from the dynamical model atmospheres reported in Sects.…”
Section: S Ori: Ud-model Fitsupporting
confidence: 92%
“…Moreover, interferometric studies of evolved-star atmospheres generally reveal the presence of at least two atmospheric layers, one corresponding to the near-continuum (used to measure the photospheric angular diameters of stars; e.g., Ohnaka et al 2009;Wittkowski et al 2017) and the other to the CO-band formation region (used to measure the star's atmospheric extension; e.g., Arroyo-Torres et al 2015). However, recent studies of the atmosphere of AGB stars have shown the presence of an intermediate layer containing weak molecular and atomic lines (e.g., Ohnaka et al 2016Ohnaka et al , 2019. Indeed, in Fig.…”
Section: Tomographic Methodsmentioning
confidence: 99%
“…We selected continuum data (CntK2 filter of the IRDIS observations and the range 2.22 − 2.28 µm for the GRAVITY data), thus excluding CO and water vapor absorption bands. Additionally we excluded some weak atomic and molecular absorption lines in the K band pseudo-continuum 62 . The angular diameter determination was done by fitting a uniform disk (UD) model to the squared visibility data only.…”
Section: Angular Diameter Determinationmentioning
confidence: 99%